INTERNATIONAL HUMANITARIAN LAW IN INTERNAL ARMED CONFLICT: IMPLEMENTING COMMON ARTICLE 3 AND ADDITIONAL PROTOCOL II TO THE GENEVA CONVENTIONS TO INTERNAL AND HORIZONTAL CONFLICTS IN INDONESIA - Heru Susetyo (terAs Law Review : Jurnal Hukum Humaniter dan HAM, 2007)
This research explores the applicability of Article 3 of the Geneva Conventions of 1949 and Additional Protocol II 1977 of the Geneva Conventions of 1949 through internal and horizontal conflicts, and the minimum threshold of'internal armed conflict and internal civil disturbances' in Indonesia, such as in Kalimantan, Paso and Maluku